The influence of information technology on the payment of zakat in Melaka - Meerangani, Khairul Azhar; Hashim, Siti Nurul Izza; Abd Wahab, Nor Azlina; Abdul Hamid, Mohammad Fahmi; Zulkefli, Ahmad Arif; Nurkhanif, Muhammad (Human Resource Management Academic Research Society, 2022)
The development of information and communication technology (ICT) has brought various benefits and conveniences to daily affairs. In addition to the communication platform, ICT is an efficient payment medium because it saves cost and time. Zakat institutions are also no exception in applying digital platforms as one of the mediums of zakat payment. Therefore, this study aims to identify the influence of information technology on the payment of zakat at the Malacca Zakat Center (PZM). The study was carried out quantitatively using a survey design with a sample size of 145 people consisting of Muslim residents aged 25 and 56 years old. Questionnaire sets were distributed to respondents in Melaka's three central districts: Alor Gajah, Melaka Tengah, and Jasin. The study results show that the Muslim community knows zakat payment activities. Furthermore, the determining factors studied showed a positive relationship to the payment of zakat in PZM, namely service quality (r=0.352, p=0.01) and information technology (r=0.408, p=0.01). Therefore, the application of efficient service quality and the information technology facilities offered can influence the payment of zakat by the community, further leading to an increase in the zakat collection rate in PZM.